x+3(2x+1)=-12

Simple and best practice solution for x+3(2x+1)=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+3(2x+1)=-12 equation:



x+3(2x+1)=-12
We move all terms to the left:
x+3(2x+1)-(-12)=0
We add all the numbers together, and all the variables
x+3(2x+1)+12=0
We multiply parentheses
x+6x+3+12=0
We add all the numbers together, and all the variables
7x+15=0
We move all terms containing x to the left, all other terms to the right
7x=-15
x=-15/7
x=-2+1/7

See similar equations:

| x+3(2x+1)=-12 | | x+3(2x+1)=-12 | | -9x+3=7x+15 | | x+3/8=13/24 | | 10x-10+9x+22=180 | | 10x-10+9x=90 | | 10x-10+9x=90 | | 7x+23=5-2x | | 7x+23=5-2x | | 15/10=n/2 | | 15/10=n/2 | | 15/10=n/2 | | 15/10=n/2 | | 3x-5-7x=31 | | 15/10=n/2 | | 15/10=n/2 | | 3x-5-7x=31 | | 3x-5-7x=31 | | 15/10=n/2 | | 3x-5-7x=31 | | (x/5)+(x)=180 | | (x/5)+(x)=180 | | (x/5)+(x)=180 | | (x/5)+(x)=180 | | (x/1-x)+(x/1+x)=0 | | 12/5x=2 | | -5(v+3)+3v+6=8v+12 | | {3y=4×+7-4×-4y=28 | | (5x+7)=(2x-2) | | 1/3x=12=-34 | | 1/3x=12=-34 | | 1/3x=12=-34 |

Equations solver categories